2013
DOI: 10.1007/978-3-642-40483-2_30
|View full text |Cite
|
Sign up to set email alerts
|

Homestead Creator: Using Card Sorting in Search for Culture-Aware Categorizations of Interface Objects

Abstract: Abstract. Designing intuitive interfaces for rural African users requires us to understand the users' conceptual model. We acknowledge differences in categorization approaches based on cultural factors, among others. In the absence of comprehensive literature and theories, we explore card sorting as a means to derive a local categorization of interface objects for one of our prototypes. Results indicate a locational-relational categorization scheme among Herero elders in Namibia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…In order to understand the underlying categorization of the signs we have engaged a group of 5 elders in the jungle in a card sorting activity. [17] and [18] have demonstrated that card sorting in a cross -cultural design context can reveal cultural adequate mental models of categorization necessary for local adaptions of design. Follo wing a generative approach all signs (either drawn or photographed, depending on the quality) were printed on individual cards and displayed all at the same time to the elders (Fig.4).…”
Section: Sign Combinati Onsmentioning
confidence: 99%
“…In order to understand the underlying categorization of the signs we have engaged a group of 5 elders in the jungle in a card sorting activity. [17] and [18] have demonstrated that card sorting in a cross -cultural design context can reveal cultural adequate mental models of categorization necessary for local adaptions of design. Follo wing a generative approach all signs (either drawn or photographed, depending on the quality) were printed on individual cards and displayed all at the same time to the elders (Fig.4).…”
Section: Sign Combinati Onsmentioning
confidence: 99%
“…Thus the representations as multimedia of real objects directed the authors to create three parallel databases. Currently we have a focus on the possible inter-cultural differences between ontologies and taxonomies as underlying structures for such databases and interface structures (for an example see Rodil et al (2013)) [34].…”
Section: D Visualizations As a Design Approachmentioning
confidence: 99%
“…Se suelen usar herramientas básicas, que incluyen materiales de papelería, tarjetas con iconos prediseñados o software específico, siendo adaptables tanto a equipos formados exclusivamente por profesionales como a entornos de colaboración con usuarios. Dependiendo del ámbito de aplicación, de la fase del proyecto y de los objetivos perseguidos se puede diferenciar entre Sociograma, para definir actores y grupos sociales presentes en un territorio concreto (Serrano, 2012;Guzmán, López & Román, 2011;Villasante, 2010); Contextual mapping, para fomentar la expresión de experiencias particulares del usuario (Scott, Bakker & Quist, 2012;Owusu, Daalhuizen & Stappers, 2012); Card sorting, para categorizar contenidos en arquitecturas de información (Sakai & Aerts, 2015;Rodil, Rehm & Winschiers-Theophilus, 2013), con variantes como el Focus Group Card Sorting (Thomas & Johnson, 2013) o el Delphi Card Sorting (Ross, 2011;Doubleday, 2013). Al igual que estas metodologías, el Máximo Escenario Común facilita la comunicación con el usuario y la visualización y organización de información relacionada con el mismo; además está enfocada a facilitar la comunicación con el equipo x-disciplinar, a definir escenarios, a relacionar actores y artefactos, y a priorizar necesidades.…”
Section: El Máximo Escenario Comúnunclassified